Perkutana zamenjava aortne zaklopke - Šušteršič, Miha (Medicinski razgledi, 2009)
Successful aortic valve replacement in the setting of aortic stenosis leads todramatic improvements of the patient's dinical condition and wellbeing. Standard surgical aortic valve replacement is a relatively safe procedure in patients with low procedural predicted risk. Because of thoracotomy, cardiopulmonary bypass, aortotomy and difficult rehabilitation, the risk of possible complications, especially in the elderly, can be high. The treatment of symptomatic aortic steno si s in high risk patients has led to alternative pathways of treating symptomatic aortic stenosis. Balloon aortic valvuloplasty, as the first attempt of definite treatment of aortic stenosis, was not very successful because it yielded only short-term results. Research continued with balloon-expandable and self-expandable aortic valve prostheses that are deployed at the site of the native aortic valve using special applicators through the peripheral vessels. This procedure has its advantages and disadvantages compared to the conventional surgical procedure, but currentresults in selected high risk patients are comparable. With new knowledge, and improved technique and instruments, outcomes can be expected toimprove in the future.
Keywords: Aortic Valve Stenosis; Aortna zaklopka, stenoza; Srce, zaklopka, proteza; Therapy; Surgery; kardiovaskularne bolezni; cardiovascular disease; Heart Valve Prosthesis; aortna stenoza; srčne zaklopke; kirurško zdravljenje